ANALISA MOMEN PUNTIR POROS IMPELLER PADA SISTEM PROPULSI WATERJET KAPAL 6 METER DENGAN VARIASI BLADE IMPELLER MENGGUNAKAN METODE CFD - Bagas Dwi Kurniawan; Jangka Rulianto; Achdri Fauzi Nugraha Oloan; I Gusti Ngurah Bagus Catrawedarma; Chairul Anam (Politeknik Negeri Batam, 2025)
Analysis of the impeller shaft torsion moment in the waterjet system with impeller blade variations aims to analyze the strength of the impeller shaft caused by the specified engine power. The engine used has a power of 6.5 hp and has an output power of 2000 Rpm. This study aims to determine the impeller shaft torsion moment with impeller blade variations using the Computational Fluid Dynamic (CFD) method. Using Aloy steel 4340 material which has a shaft diameter of 23 mm and a length of 700 mm. The torque value that appears in variation 1 with 3 impeller blades is 30.65 Nm, variation 2 with 4 impeller blades is 87.61 Nm and for variation 3 with 5 impeller blades is 33.07 Nm. In accordance with the results of the calculation of the torsion moment of 30.85 Nm, it is known that variation 1 with 3 impeller blades is said to meet the specified criteria to be applied to the waterjet system. Based on the results of the specified allowable stress of 60.89 Nm, it was found that for variations 1 and 3 with the number of impeller blades of 3 and 5 respectively, they have met the safe conditions for the impeller shaft torsion moment, by considering that variation 3 is adjusted to the results of the impeller shaft torsion moment calculation to determine the effectiveness for the specified waterjet system.